CRISPR-Cas9 screen reveals that inhibition of enhancer of zeste homolog 2 sensitizes malignant T cells to dimethyl-fumarate-induced cell death - Teubner, Jan P.; Tümen, Deniz; Kandulski, Arne; Heumann, Philipp; Mester, Patricia; Aschenbrenner, Elisabeth; Pollinger, Kirstin; Gunckel, Manuela; Volz, Barbara; Hein, Tobias; Beltzig, Paul L.; Tengler, Luisa; et al. (The FEBS journal, 2025)
Constitutive activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway is a hallmark of many lymphocyte-associated cancers, including cutaneous T-cell lymphoma (CTCL) and its leukemic variant, the Sézary syndrome. Dimethyl fumarate (DMF) has been identified as a promising NF-κB-targeted therapy and has shown positive outcomes in a phase II clinical trial involving patients with Sézary syndrome. However, limited responsiveness remains a significant challenge. Through a genome-wide clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 screen, we identified enhancer of zeste homolog 2 (EZH2; also known as histone-lysine N-methyltransferase) as a critical target for enhancing DMF-induced cell death. EZH2, the catalytic subunit of Polycomb Repressive Complex 2 (PRC2), is responsible for the methylation of histone H3 (H3K27). Combining DMF with the US Food and Drug Administration (FDA)-approved EZH2 inhibitor tazemetostat significantly increases cell death in patient-derived CTCL cells, offering a promising strategy to improve therapeutic outcomes and overcome limited responsiveness to DMF.
Erstmals veröffentlicht: 1. August 2025
Gesehen am 30.10.2025